2003
DOI: 10.1177/002204260303300308
|View full text |Cite
|
Sign up to set email alerts
|

Drug Consumption Rooms in Hamburg, Germany: Evaluation of the Effects on Harm Reduction and the Reduction of Public Nuisance

Abstract: In order to evaluate the impact of consumption rooms (CRs) on the promotion of health among drug users and the reduction of the public nuisance of drug use, a study examining CRs in three countries was carried out in 2000. The study, supported by the European Commission, examined CRs in Rotterdam (The Netherlands), Innsbruck (Austria), and Hamburg (Germany). This paper evaluates the findings from the study of Hamburg CRs. In order to get evidencebased information on the effects of CRs, 616 drug users in the Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 3 publications
2
57
0
1
Order By: Relevance
“…In Germany, a survey conducted in 2002 among clients of 18 DCRs in different cities found 80% of clients with more than 1 visit/week [23] ; another study conducted in Hamburg in the DCRs of the city and their immediate surroundings [12] found that one third of the clients were daily users, one third occasional users (one to several visits per week) and one third less than once a week or never. In the Netherlands an average of 6 visits/week was found among pass holders of DCRs in Rotterdam [11] , and in Switzerland, in a survey among the clients of the Biel DCR in 2002, 43% were daily visitors [24] , and in the DCRs of Zurich in 2002, the mean visit frequency was more than 5/week [1] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Germany, a survey conducted in 2002 among clients of 18 DCRs in different cities found 80% of clients with more than 1 visit/week [23] ; another study conducted in Hamburg in the DCRs of the city and their immediate surroundings [12] found that one third of the clients were daily users, one third occasional users (one to several visits per week) and one third less than once a week or never. In the Netherlands an average of 6 visits/week was found among pass holders of DCRs in Rotterdam [11] , and in Switzerland, in a survey among the clients of the Biel DCR in 2002, 43% were daily visitors [24] , and in the DCRs of Zurich in 2002, the mean visit frequency was more than 5/week [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of DCRs is known to vary according to the characteristics of the services provided: size and location of the premises (especially the proximity of the drug market) [1] , waiting times [12] , opening hours [1] , general accessibility to syringes [25] or the population targeted (e.g. illegal immigrants in specialized structure in the Netherlands) [26] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations